Implicated Memory Activism Across Borders: South Korean Advocacy for Vietnamese Massacre Victims of the Second Indochina War - Phan, Xuan-Dung (Millennium, 2025)
Despite growing scholarly interest in memory activism by implicated subjects – those indirectly entangled in systems of power and historical injustices without being direct perpetrators – existing studies have predominantly focused on national domestic contexts. This article explores how such activism functions transnationally by focusing on the case of South Korean civil society advocacy for Vietnamese victims of massacres committed by the Republic of Korea during the Second Indochina War. Drawing on interviews with memory activists and extensive secondary sources, I trace how South Korean implicated subjects drew on repertoires of contention to challenge state-led strategic amnesia over the past three decades, thereby fostering greater commemoration and recognition of the victims. I argue that these memory activists leveraged two mechanisms: cultural memory mobilisation – the strategic invocation of locally and globally circulating historical memories to create empathetic bridges with the victimised other – and transnational tactical adaptation – the application, modification and transfer of mnemonic practices across national boundaries. Their agency was enabled and constrained by structural conditions engendered by South Korea’s democratisation and Vietnam’s economic liberalisation in the late 1980s. Theoretically, this article develops an analytical framework for transnational implicated memory activism. Empirically, this article explores a case of grassroots advocacy surrounding atrocities committed during the Second Indochina War, a subject that has been overlooked in memory studies.